Synthesis and Characterization of Mixed Ligand Complexes of Co(II) and Fe(III) Ions with Malic Acid and Heterocyclic Amines (Bangladesh Pharmaceutical Journal, 2012)
This paper describes the preparation and characterization of mixed ligand complexes of Co(II) and Fe(III) ions with malic acid and heterocyclic amines. The general formula of the complexes are as follows: [M(MA)L2] and K[M(MA)2L2] (where, M = Co(II) (1-4), Fe(II) (5-8); MA = C4H4O5 (1-4), 2C4H4O5 (5-8); L = C6H5N (1), C6H7N (2), C9H7N (3, 4), 2C6H5N (5), 2C6H7N (6), 2C9H7N (7-8). The complexes were prepared in the solid form and characterized by elemental analysis, conductivity and magnetic measurements, infrared and electronic spectroscopic studies. The infrared spectra of the complexes confirmed the coordination of metal ion with ligands. The Co(II) complexes are assumed to have tetrahedral and the Fe(III) complexes have octahedral structure based on the electronic spectra and magnetic measurements. Their antibacterial and antifungal activity has also been evaluated by the disc diffusion methods against fourteen pathogenic bacteria (five gram positive and nine gram negative) and fourteen fungi. Complexes [Co(II)(MA)(4-pico)2] showed the highest antibacterial activity against all bacteria tested (when, MA= C4H4O5 and 4-pico = C6H7N). DOI: http://dx.doi.org/10.3329/bpj.v15i2.12589 Bangladesh Pharmaceutical Journal 15(2): 177-181, 2012